Očesne spremembe v nosečnosti - Dobovšek, Darja (Zdravniški vestnik, 2012)
Pregnancy is often associated with ocular changes which are mostly transient but in some cases permanent. The ocular changes in pregnancy are either physiological or pathological. Pregnancy can improve or exacerbate the pre-existing ocular conditions. Pregnancy per se is associated with a hypercoagulable state and this may lead to occlusive vascular diseases of the choroid and retina. Diabetic retinopathy may result in worsening of the disease during pregnancy. On the other hand, there can be improvement of opticneuritis, uveitis, glaucoma or thyroid orbitopathy. Physiological changesinclude periocular skin, corneal and lens changes or changes in the intraocular pressure and visual field. Pathological changes include central serous retinopathy. Preeclampsia, eclampsia and HELLP syndrome are gestationaldiseases, which can also manifest themselves with ocular symptoms. Spontaneous vaginal delivery is not contraindicated in pregnant women with risk factors for retinal detachment if appropriate care is given before delivery, as necessary.
Keywords: diabetična retinopatija; nosečnost; očesne spremembe; odstop mrežnice; preeklampsija